A Review on Transformerless Step-Up Single-Phase Inverters with Different DC-Link Voltage for Photovoltaic Applications - Wenjie Liu; Kamran Ali Khan Niazi; Tamas Kerekes; Yongheng Yang (Energies, 2019)
Photovoltaic (PV) energy has been competitive in power generation as an alternative to fossil energy resources over the past decades. The installation of grid-connected solar energy systems is expected to increase rapidly with the fast development of the power electronics technology. As the key to the interface of the PV energy and the grid, power converters should be reliable, efficient and comply with the grid requirements. Considering the nature of PV energy, the power conversion should be flexible (e.g., high step-up DC-DC conversion and harmonic-free DC-AC conversion). Accordingly, many power electronic converters have been reported in literature. Compared with isolated inverters, transformerless inverters show great advantages. This paper thus presents an overview of the transformerless step-up single-phase inverters for PV applications based on the dc-link configurations. Grid-connected PV inverters are classified as constant dc-link voltage structures, pseudo-dc-link voltage structures, pulsating dc-link voltage structures and integrated dc-link voltage structures. The discussion on the composition of different dc-link structures is presented, which provides guidance to select appropriate transformerless inverter topologies for PV applications.